Desigualdad social y transición de la escuela al trabajo en la Ciudad de México - Solís Gutiérrez, Patricio (El Colegio de México, 2012)
Works on social inequality in Latin America have mainly studied the inequality of condition, apart from the mechanisms that contribute to the persistence of inequality over time. It has been suggested that to identify these mechanisms it is necessary to analyze the inequality of opportunities, in other words, how gaps of origin in social circumstances become socially heterogeneous destinations. Based on the life course perspective, in this paper I explore the magnitude of the effects of the social circumstances of origin of a set of educational and occupational outcomes occurred during the phase of the course of life known as school-work transition (age when leaving school, years of schooling, age of entry to work, and social class of entry to work). The analysis indicates that even in an environment with higher relative abundance of opportunities as Mexico City, it remains a close association between social origins inequality and inequality in these outcomes, even after controlling for a number of sociodemographic variables. These results help to highlight the importance of the transition from school to work as a crucial stage in the process of intergenerational transmission of inequality over the life course.